Erythropoietin: An Historical Overview of Physiology, Molecular Biology and Gene Regulation - Mole, D; Ratcliffe, P (Elsevier, 2008)
This chapter presents a historical study on erythropoietin. It was only a few years after the concept of hormone was first suggested by Henri Brown-Sequard in 1889 that the idea of hormonal regulation of erythropoiesis was first formulated by Carnot and Deflandre in 1906. Early erythropoietin research was hampered by the low concentration of the hormone in the fluids and tissues to be studied, particularly in the basal state, which made its detection and quantitation unreliable. The first assays of erythropoietin activity utilized the rate of incorporation of radioactive iron-59 into hemoglobin as a measure of erythropoiesis in starved rats that had been injected with the material under test. Armed with the early bioassays of erythropoietic activity, researchers next turned their attention to the biochemical purification of erythropoietin. Early attempts at partial purification of erythropoietin from anemic rabbit serum proved remarkably informative. The erythropoietic activity was found to have an electrophoretic mobility similar to alpha-2 globulin, to be heat stable, and to stain for carbohydrate. Erythropoietin was therefore deduced to be a glycoprotein. These studies also showed that erythropoietin contained hexose, hexosamine, and sialic acid and that erythropoietic activity was lost upon removal of neuraminic acid. © 2009 Elsevier Inc. All rights reserved.